ISLAMIC BOARDING SCHOOL'S MANAGEMENT CASE STUDY IN ISLAMIC BOARDING SCHOOL - Tamjidillah HM Amin (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
This study aims to gain a deep understanding of the Management of Pondok Pesantren Abu Hurairah Mataram and more specifically is to understand in depth about curriculum management, teacher management and educational staff, infrastructure management, financial management and student management at boarding school Abu Hurairah Mataram. This type of research is qualitative research with intrinsic design of Case Study. Data collection techniques: Interview, Observation and Documentation. The collected data is examined and researched through Triangulation. Furthermore, the data is organized, interpreted, and concluded so as to produce (1) Curriculum Management at Pondok Pesantren Abu Hurairah Mataram apply KTSP management but more emphasized on Takhassus curriculum (Curriculum Pondok Pesantren) (2) Management of educators and educational staff is more emphasis on recruitment of educators And educational personnel conducted through the tests of intellectual ability, language and talent and interests, have loyalty, selfless spirit (3) Financial management implements open management oriented to the values ​​of justice, honesty and sincere support the management of accountable and transparent .